Instruction to appoint experienced architect and MEP engineer to supervise the finishing works and MEP works - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the instruction to appoint experienced architect and MEP engineer to supervise the related works of BRACU new campus project.